Would a move into the United Kingdom’s road-going electric light commercial vehicle market represent a sensible strategic move for Bradshaw Electric Vehicles? - Dalton, Matthew J (2011)
Bradshaw Electric Vehicles has been successfully making and trading in electric vehicles for roughly 50 years. Their site at Stibbington, near Peterborough, is a clear representation of industrial efficiency – producing a wide variety of vehicles that are highly tailored to customers’ requirements.The company’s 2010 published accounts show a healthy profit, representing its strong trading reputation.